The Expanding Role of Percutaneous Left Atrial Appendage Closure for Stroke Prevention in Patients with Atrial Fibrillation: A Review. Issue 4 (4th July 2021) - Ha, Francis J.; Sanders, Lauren M.; Palmer, Sonny C.
ABSTRACT: Atrial fibrillation (AF) is the most common arrhythmia in older people. Oral anticoagulation reduces the risk of ischemic stroke in patients with sufficient thromboembolic risk however is associated with bleeding. Because the left atrial appendage (LAA) is considered the predominant source of thromboembolism in AF, percutaneous closure of the LAA has been proposed as a potential therapy to reduce the risk of ischemic stroke. Clinical uptake of percutaneous LAA closure has been limited due to initial safety concerns, requirement of temporary anticoagulation post-implantation, and lack of prospective randomized data that used non-vitamin K oral antagonists for comparison. Recently published trial data address some of these limitations and provides additional information to aid in clinical decision-making. We summarize the growing body of evidence that suggests percutaneous LAA closure is an effective, safe alternative in patients with AF and contraindications to lifelong oral anticoagulation.